Destination competitiveness, tourism facilities and problems in promoting Uttarakhand as a tourism destination / Bindu Roy and A.K. Saxena - Roy, Bindu; Saxena, A.K. (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2020)
The main objective of this paper is to identify Uttarakhand destination competitiveness, tourism facilities and problems faced by the tourism department in promoting Uttarakhand. One hundred stakeholders from the five major cities of Uttarakhand were surveyed using the random sampling method. For the analysis of data collected by questionnaires, the researcher has applied both descriptive and advanced statistical techniques. The findings revealed that there were significant differences amongthe perceptions of stakeholders in the field of tourism in Uttarakhand. As per the stakeholders’ opinions, Uttarakhand tourism is facing various sorts of problems, mainly economic, political, environmental, infrastructural and social issue. It may be also helpful for the government in taking implementing suggestive measures for the promotion and development of tourism sector, which might then satisfy the stakeholders.